ANALISIS NILAI TAMBAH USAHA INDUSTRI PENGOLAHAN IKAN ASIN “MINOARTO” DIDESA SIDIKAYA KECAMATAN CILACAP SELATAN KABUPATEN CILACAP - Vandrias Dewantoro; Vini Arumsari; Rahma Widiarti (Jurnal Dinamika Sosial Ekonomi, 2010)
Analysis added value of Effort Industry Processing of briny Fish “Minoarto” in Countryside of Sidikata District of cilacap South Sub-Province ofCilacap. This research have to know the level of effciecy of effort industry processing of briny fish "Minoarto”, knowing the level of obtained added value of sale of briny fish and kinow constraints faced the effort industry processing of briny fish "Minoarto”. Method research the used is descriptive. For method or determination of area use method of purposive sampling. First target to know the feel of efficiency of effort briny use formula of RC ratio, while second target to know the level of added value use formula of incremental RC ratio. Effort industry processing of briny fish in Countryside of Sidikaya District of Cilacap South Sub-Province of Cilacap obtain get reenue equal to Rp 108.560.962,50 and value of R/C equel 1,81 meaning the effort processing of this briny fish have efficient because value of R/C> 1.. Effort industry processing of briny fish "Minoarto” can give added value compared to the effort sale of fresh fish, with value of incremental R/C equel to 1,49 and advantage difference equel to 49.695. 712,50 In managing the effort briny fish industry "Minoarto" facing constraints for example usage of production appliances which still traditional, and limitation of capital.Keyword : industry briny fish, added value, efficiency constraints